Implementation and Effectiveness of English Education Innovations at Madrasah Aliyah Darul Ulum Kota Banjar - Sri Gusmayanti, Aneu (TarbiyahMU, 2024)
This study aims to examine the implementation and effectiveness of English education innovations at Madrasah Aliyah Darul Ulum Kota Banjar. Using a qualitative approach with a case study design, data were collected through in-depth interviews, classroom observations, and document analysis. The findings indicate that innovations such as the use of online learning technologies, video learning, flipped classrooms, and project-based learning have successfully enhanced students' motivation, engagement, and English language skills. However, several challenges were identified in the implementation of these innovations, including limited access to technological devices, insufficient ongoing teacher training, and inadequate technological infrastructure. The study concludes that educational innovations have significant potential to improve the quality of English education, but there needs to be enhanced technological access, continuous teacher training, and strengthened infrastructure to overcome existing challenges.